GAMBARAN POLA PENERIMAAN PENEGAKAN DIAGNOSTIK DAN TINDAKAN TERAPI KANKER OLEH DOKTER PADA PENDERITA KANKER PAYUDARA DI RSU DOKTER SOEDARSO PONTIANAK - ., Metha Isdamayanti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Backgrounds?Breast cancer is the most frightening disease by all of women. To begin the therapy is very influence of age, education, emotional reaction, and time period. Because of that, the data about acceptance pattern is needed.Objective?To collect data about description of age, education, emotional reaction, and acceptance time period of therapy to breast cancer patients in Soedarso General Hospital Pontianak.Method?A kind of descriptive research with cross sectional design. The data was fetched by interview breast cancer patients who have begun therapy in Soedarso General Hospital Pontianak.Results?There were 64 patients included as samples of this research. The most often age group is 40-49 years old (51,6%) with the average age is 47,34 years old. Senior high school is the most often education level (34,4%) of the patients. All of the patients passed through acceptance phase (100%) and the most often time period is first trimester (81,25%).Conclusion?Most of patients are between 40-49 years old (51,6%), with the most often education level is senior high school. All of the patients passed through the acceptance phase and first trimester is the most often time period that needed by them.Keywords : breast cancer, age, education, emotional reaction, time period